Reducing Dark Conductivity of Cesium Tin Halide Perovskites with Donor Doping - John L. Lyons; Michael W. Swift; Anderson Janotti; Mercouri G. Kanatzidis (PRX Energy)
The inorganic tin halide perovskites (such as CsSnBr_{3} and CsSnI_{3}) exhibit high hole concentrations, which have been attributed to the presence of intrinsic defects such as cation vacancies. Despite their promise as photovoltaic materials, this high intrinsic conductivity limits deployment. Using hybrid density functional theory, we examine the impact of these intrinsic defects on the electronic properties of CsSnBr_{3} and CsSnI_{3}. We find that tin and cesium vacancies have low formation energies, especially under Sn-poor conditions, in agreement with prior work, and that the presence of these native acceptor defects can lead to high hole concentrations. However, effective donor doping of these systems can be obtained via Sc or Y incorporation. These impurities substitute on the Sn site, where they act as single donors. By examining the formation energy of these dopants versus the native defects, we show that Sc or Y doping should lead to a strong compensation, reducing hole concentrations under Sn-rich conditions.